Anatomical Predictors of Pacemaker Dependency After Transcatheter Aortic Valve Replacement. (January 2021) - Nai Fovino, Luca; Cipriani, Alberto; Fabris, Tommaso; Massussi, Mauro; Scotti, Andrea; Lorenzoni, Giulia; Guerra, Maria Chiara; Cardaioli, Francesco; Rodinò, Giulio; Matsuda, Yuji; Masiero, Giulia; Leoni, Loira; et al.
Abstract : Background: Conduction disturbances after transcatheter aortic valve replacement (TAVR) are often transient. Limited data exist on anatomic factors predisposing to pacemaker dependency after TAVR. We sought to assess the rate and the possible predictors of pacemaker dependency after TAVR. Methods: Consecutive patients undergoing pacemaker implantation up to 30 days after TAVR between May 2014 and September 2019 were included. Baseline electrocardiographic, computed tomography, and procedural characteristics were collected, including valve implantation depth and membranous septum length, an anatomic surrogate of the distance between the aortic annulus and the His bundle. Pacemaker dependency at 30 days and 1 year and all-cause mortality during follow-up were evaluated. Results: Of 728 TAVR patients, 112 (53.5% men; median age, 81 years) underwent pacemaker implantation after TAVR. Of these, 44.6% (50 of 112) were pacemaker dependent at 30 days and 46.7% (36 of 77) at 1 year. By multivariate analysis, independent predictors of 30-day pacemaker dependency included left ventricular outflow tract calcifications under the left coronary cusp (odds ratio, 5.69 [95% CI, 1.45–22.31]; P =0.013) and a difference between membranous septum length and implantation depth (ΔMSID) ≥3 mm (odds ratio, 7.58 [95% CI, 2.07–27.78]; P =0.002). Conversely, membranous septum length and implantation depth alone were not associated with pacemaker dependency (odds ratio, 0.79 [95% CI, 0.60–1.05]; P =0.11 and odds ratio, 1.11 [95% CI, 0.99–1.24]; P =0.08). At a median follow-up of 28.1 (11.7–48.6) months, pacemaker-dependent patients did not show a worse survival ( P =0.26). Conclusions: Less than half of the patients undergoing pacemaker implantation after TAVR are pacemaker-dependent at midterm follow-up. ΔMSID ≥3 mm and the presence of left ventricular outflow tract calcifications under the left coronary cusp, but not membranous septum length nor implantation depth alone, are predictive of long-term pacemaker dependency after TAVR, thus influencing device selection and programming. Abstract : Supplemental Digital Content is available in the text.